Cone-beam computed tomography study of the incidence and characteristics of the second mesiobuccal canal in maxillary permanent molars - Xu, Yuan-Qing; Lin, Jie-Qi; Guan, Wei-Qun (Frontiers in Physiology, 2022)
Objective: This study aimed to review the characteristics of the second mesiobuccal canal (MB2) in the maxillary first and second permanent molars of 500 patients to analyze the incidence of MB2 and its connection with gender, age, tooth position, and mesiobuccal (MB) root length. The study also aimed to investigate the distribution of the root canal orifice on the pulp chamber floor to obtain an imaging reference for clinical practices related to maxillary molars in Fujian, China. Methods: In accordance with the enrollment criteria, cone-beam computed tomography images of the maxillofacial area were collected from 500 patients, including 1,000 maxillary first molars and 1,000 maxillary second molars. The patients were grouped according to gender and tooth position. The incidence of MB2 was observed, and the MB root length and distribution angle of the mesiobuccal-palatal-distobuccal root canal orifices were measured for statistical analysis. Results: The overall incidence of MB2 in maxillary first and second molars was 51.1% and 32.9%, respectively. The incidence of MB2 in maxillary molars was 50% in male patients and 35.45% in female patients, with a significant difference (P < 0.05). The incidence of MB2 in maxillary first molars was significantly higher in subjects aged below 50 (especially in male patients) than those aged 50 and above. The MB root length of maxillary first and second molars with MB2 was longer than that without MB2, and the difference was statistically significant. An association was identified between the incidences of MB2 in contralateral molars of the same type and in ipsilateral adjacent molars. When MB2 occurred in the MB root of maxillary molars, the root canals were mostly classified as type IV, followed by type II. The angle formed by the MB-P-DB orifices on the pulp chamber floor in the maxillary first and second molars was (25.23 ± 5.20)° and (20.17 ± 10.88)°respectively. Conclusion: The incidence of MB2 in maxillary molars is high in Fujian, China. The occurrence of MB2 is affected by gender, age, and length of MB root, and it occurs symmetrically in adjacent molars and in contralateral molars of the same type. In addition, the